Positive electrode material and secondary battery

By using a positive electrode material containing lithium manganese iron phosphate and moderate nickel content in the secondary battery, and adding an appropriate amount of vinyl carbonate to the electrolyte, the problems of low gram capacity and poor circulation performance of lithium manganese iron phosphate are solved, and significant improvements in capacity and circulation performance are achieved.

CN119786506APending Publication Date: 2025-04-08AESC DYNAMICS TECHNOLOGY (HUBEI) LTD +2
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202311221265.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-20
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The gram capacity of lithium manganese iron phosphate material is low, has poor conductivity and large polarization, which makes it difficult to perform the cycling performance of secondary batteries, and requires matching different electrolyte designs to avoid attenuation acceleration.

Method used

A positive electrode material including lithium manganese iron phosphate and the second active substance LixNiyCozMkMepOrAm is used, and the nickel content in the second active substance is designed to be between 0.81 and 0.91, and the positive electrode material is matched by making the vinylene carbonate in the electrolyte account for 1% to 4% of the total mass.

Benefits of technology

The gram capacity and circulation performance of the secondary battery are significantly improved, and the capacity of more than 85% is still maintained after 4,000 cycles, avoiding special requirements for electrolyte design.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786506A_ABST
    Figure CN119786506A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode material, which comprises: a first active material, which is lithium manganese iron phosphate; the chemical formula of the second active substance is LixNiyCozMkMepOrAm, x is larger than or equal to 0.85 and smaller than or equal to 1.15, y is larger than or equal to 0.81 and smaller than or equal to 0.91, z is larger than 0 and smaller than 1, k is larger than 0 and smaller than 1, p is larger than or equal to 0 and smaller than or equal to 0.1, r is larger than or equal to 1 and smaller than or equal to 2, m + r is larger than or equal to 0 and smaller than or equal to 1, y + z + k + p = 1, M is one or two of Mn and Al, Me is one or more of Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W and Nb, and A is one or more of N, F, S and Cl. The positive electrode material provided by the invention improves the cycle performance of the corresponding secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Embodiments of the present application relate to the field of batteries, and more specifically, to positive electrode materials and secondary batteries. Background Art

[0002] In recent years, with the rapid development of new energy sources at home and abroad, especially the power batteries related to the electric vehicle industry, lithium iron phosphate (LiFePO4) materials have been difficult to meet the different needs of people for the range of electric vehicles due to their own shortcomings, such as low operating voltage (3.4V) and low battery energy density. On this basis, by replacing part of the iron element in the lithium iron phosphate material with manganese to form lithium iron manganese phosphate (LiMn x Fe (1-x) PO4, where 0<x<1) materials are used to improve energy density. Therefore, in order to meet the increasing energy density demand in the field of new energy vehicles, lithium iron manganese phosphate materials have attracted much attention because they have the same advantages as lithium iron phosphate materials, such as safety and low cost. Compared with lithium iron phosphate materials, lithium iron manganese phosphate materials have a higher voltage platform (4.1V), better low temperature performance, and an energy density close to that of five-series ternary materials (for example, LiNi 0.5 Co 0.2 Mn 0.3 O2 positive electrode material).

[0003] Nevertheless, the gram capacity of lithium manganese iron phosphate material is low (170mAh / g), and it is currently mixed with some other positive electrode materials (for example, NCM ternary materials, the general formula is LiNi x Co y Mn z O 2, Among them, x+y+z=1) is used to improve the gram capacity, but the improvement effect is limited. Therefore, relevant improvements are needed to further improve the gram capacity and cycle performance of the corresponding positive electrode material.

[0004] Furthermore, in the prior art, the positive electrode material of this hybrid system needs to be designed with a special electrolyte to fully exert its performance, especially the cycle performance. Specifically, since the conductivity of lithium manganese iron phosphate material is not as good as lithium iron phosphate, the degree of polarization during discharge is relatively large, which makes it difficult to exert the capacity. At the same time, the attenuation mechanisms of the positive electrode materials of this hybrid system are different, so different electrolyte designs need to be matched, otherwise the battery is prone to accelerated attenuation, resulting in technical problems that the performance (especially the cycle performance) is difficult to exert. In summary, a secondary battery including an electrolyte related to the positive electrode material is also urgently needed to solve the above problems. Summary of the invention

[0005] In order to overcome the above problems existing in the prior art, some embodiments of the present application provide a positive electrode material, including: a first active material, the first active material is lithium manganese iron phosphate; and a second active material, the chemical formula of the second active material is Li x Ni y Co z M k Me p O r A m , wherein 0.85≤x≤1.15, 0.81≤y≤0.91, 0<z<1, 0<k<1, 0≤p≤0.1, 1≤r≤2, 0≤m≤1, m+r≤2, y+z+k+p=1, M is selected from one or two of Mn and Al, Me is selected from one or more of Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, and Nb, and A is selected from one or more of N, F, S, and Cl.

[0006] In the above positive electrode material, 0.82≤y≤0.86.

[0007] In the above positive electrode material, the median particle size of the first active material is smaller than the median particle size of the second active material.

[0008] In the above positive electrode material, the median particle size of the first active material ranges from 0.5 μm to 0.9 μm, and the median particle size of the second active material ranges from 5 μm to 8 μm.

[0009] In the above positive electrode material, the first active material is around the second active material, and the cross-sectional perimeter of the coated second active material accounts for more than 90%.

[0010] In the above positive electrode material, M is Mn or Al.

[0011] In the above-mentioned positive electrode material, the general formula of the lithium manganese iron phosphate is LiMn q Fe (1-q) PO4, where 0.6≤q≤0.8.

[0012] In the above positive electrode material, the percentage of the first active material in the total mass of the positive electrode material is greater than or equal to 70% and less than 100%.

[0013] In the above positive electrode material, the median particle size of the primary particles of the first active material ranges from 0.1 μm to 0.4 μm.

[0014] Other embodiments of the present application also provide a secondary battery, comprising: a positive electrode plate, the positive electrode plate comprising the above-mentioned positive electrode material; a negative electrode plate; a separator, located between the positive electrode plate and the negative electrode plate; and an electrolyte, wherein the percentage of vinylene carbonate in the electrolyte to the total mass of the electrolyte is greater than or equal to 1% and less than or equal to 4%.

[0015] The positive electrode material provided in the embodiment of the present application can improve the gram capacity and cycle performance of the corresponding secondary battery, but the improvement effect is limited. Based on this, the present application also provides a secondary battery with a positive electrode material and an electrolyte having a mutually matching design, which can significantly improve the cycle performance of at least the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 A schematic cross-sectional view passing through the center of a positive electrode material particle according to an embodiment of the present application is shown.

[0017] Figure 2 The cycle performance diagram of the secondary batteries according to Examples 1, 12, 15-16 and Comparative Example 1 of the present application after 4000 cycles is shown. DETAILED DESCRIPTION

[0018] The following examples may enable those skilled in the art to more fully understand the present application, but do not limit the present application in any way. The percentages used below are all mass percentages unless otherwise specified.

[0019] At present, secondary batteries are used more and more widely, such as mobile phones, tablet computers, wearable devices, mobile power supplies, electronic cigarettes, digital products, power tools, power devices, energy storage devices and other products, and are particularly important in the field of new energy. With the development of secondary batteries, the requirements for the cycle performance of secondary batteries are getting higher and higher. In secondary batteries, positive electrode sheets, negative electrode sheets, separators and electrolytes are usually included. The positive electrode sheet generally includes a positive electrode collector and a positive electrode material arranged on the positive electrode collector. Lithium batteries are divided according to the positive electrode material system, mainly divided into lithium cobalt oxide (LCO), lithium manganese oxide (LMO), lithium iron phosphate (LFP), ternary materials (nickel cobalt manganese oxide (NCM) and nickel cobalt aluminum oxide (NCA)), etc. Among the above-mentioned positive electrode materials, lithium iron manganese phosphate has become a secondary battery positive electrode active material with a very broad market prospect due to its low raw material cost and good safety. In particular, the design of soft packs, square hard shells and cylindrical batteries involves the application of lithium iron manganese phosphate materials in the lamination and winding of secondary batteries. However, when lithium iron manganese phosphate is used as a positive electrode active material, its development is restricted by technical problems such as its low gram capacity (170mAh / g), poor conductivity, and large polarization. There are currently some improved technologies, for example, by mixing NCM ternary active materials into lithium iron manganese phosphate active materials to improve gram capacity. However, due to the differences in their respective attenuation mechanisms, the positive electrode materials of this mixed system need to match different electrolyte designs, otherwise it is very easy to accelerate attenuation, so there are technical problems that performance (especially gram capacity and cycle performance) is difficult to play out. Therefore, there is an urgent need for a new positive electrode material to solve the above problems. In addition, for the corresponding lithium-ion battery, it is also necessary to design an electrolyte that matches the positive electrode material of the mixed system to give full play to its performance, especially the performance of cycle performance.

[0020] The inventors of the present application have found that the positive electrode material can be made to include a first active material of lithium manganese iron phosphate and a second active material, wherein the chemical formula of the second active material is Li x Ni y Co z M k Me p O r A m, wherein, 0.85≤x≤1.15, 0.81≤y≤0.91, 0<z<1, 0<k<1, 0≤p≤0.1, 1≤r≤2, 0≤m≤1, m+r≤2, y+z+k+p=1, M is selected from one or two of Mn and Al, Me is selected from one or more of Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, and Nb, and A is selected from one or more of N, F, S, and Cl. In the positive electrode material provided in the present application, the content of Ni in the second active material is designed to be between 0.81 and 0.91 (0.81≤y≤0.91), which can effectively improve the gram capacity of the positive electrode material. In addition, the use of the second active material also partially improves the cycle performance of the secondary battery including the corresponding positive electrode material.

[0021] In a further embodiment, the secondary battery provided by the present application further includes an electrolyte matching the above-mentioned positive electrode material, and the cycle performance of the secondary battery is further significantly improved by making the percentage of vinylene carbonate in the electrolyte greater than or equal to 1% and less than or equal to 4% of the total mass of the electrolyte.

[0022] The secondary battery provided by the embodiment of the present application can be a square hard-shell battery, a soft-pack battery, a cylindrical battery, etc. The secondary battery has excellent cycle performance, and after 4000 charge and discharge cycles, still has a capacity retention rate of 85%.

[0023] Specifically, an embodiment of the present application provides a positive electrode material, including: a first active material of lithium manganese iron phosphate, and a second active material, wherein the chemical formula of the second active material is Li x Ni y Co z M k Me p O r A m, wherein 0.85≤x≤1.15, 0.81≤y≤0.91, 0<z<1, 0<k<1, 0≤p≤0.1, 1≤r≤2, 0≤m≤1, m+r≤2, y+z+k+p=1, M is selected from one or two of Mn and Al, Me is selected from one or more of Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, Nb, and A is selected from one or more of N, F, S, and Cl. As described above, the nickel content in the second active material in the positive electrode material is between 0.81 and 0.91, which not only increases the gram capacity of the positive electrode material, but also the use of the second active material partially improves the cycle performance of the secondary battery including the corresponding positive electrode material. In some embodiments, 0.82≤y≤0.86, that is, the nickel content in the second active material in the positive electrode material is between 0.82 and 0.86, wherein when the nickel content is between 0.82 and 0.86, the gram capacity of the secondary battery is improved better. In some embodiments, the first active material accounts for a percentage of greater than or equal to 70% and less than 100% of the total mass of the positive electrode material. In some embodiments, the general formula of lithium manganese iron phosphate in the first active material is LiMn q Fe (1-q) PO4, wherein 0.6≤q≤0.8. That is, the manganese content in the first active material is between 0.6 and 0.8.

[0024] In some embodiments, the median particle size (Dv50) of the first active substance is smaller than the median particle size of the second active substance. The median particle size refers to the particle size corresponding to when the cumulative volume particle size distribution percentage of a sample (the first active substance or the second active substance) reaches 50%, and the unit of measurement is μm. In some embodiments, the median particle size of the first active substance ranges from 0.5μm to 0.9μm, and the median particle size of the second active substance ranges from 5μm to 8μm. In some embodiments, the first active substance is coated around the second active substance, and the cross-sectional circumference of the coated second active substance accounts for more than 90%. That is to say, in this embodiment, by selecting a positive electrode material of a particle size range (the median particle size of the first active material is much smaller than the median particle size of the second active material) and making the cross-sectional circumference of the coated second active material account for more than 90%, there are only small particles of the first active material around the second active material particles, and the large particles of the second active material play a role similar to that of a pillar in the first active material particles. It can be seen that the positive electrode material of the present application reduces polarization and improves the compaction density by mixing large and small particles through the selection of large particles of the second active material and small particles of the first active material. In some embodiments, the first active material includes primary particles and secondary particles formed by the primary particles. In some embodiments, the median particle size of the primary particles of the first active material ranges from 0.1μm to 0.4μm. In an embodiment, Figure 1 A schematic cross-sectional view through the center of a positive electrode material particle 30 including a first active material 10 and a second active material 20 according to an embodiment of the present application is shown. As shown in the figure, the first active material 10 is coated on the surface of the second active material 20 to form the positive electrode material particle 30. In some embodiments, the positive electrode material particle 30 has a first diameter D1, and the second active material 20 has a second diameter D2. In some embodiments, the cross-sectional perimeter of the coated second active material 20 accounts for more than 90%, which means that when the first active material 10 coats the second active material 20 to form the positive electrode material particle 30, in the cross-section passing through the center of the positive electrode material particle 30, the perimeter (πD1) of the second active material 20 is greater than 90% of the perimeter (πD2) of the positive electrode material particle 30. Although in Figure 1 In FIG. 1 , the first active material 10 and the second active material 20 are shown as round particles, but the first active material 10 and the second active material 20 may be in any shape.

[0025] In some embodiments, M in the second active material may be Mn (manganese). That is, the second active material may be lithium nickel cobalt manganese oxide. In other embodiments, M in the second active material may be Al (aluminum). That is, the second active material may be lithium nickel cobalt aluminum oxide. In still other embodiments, the second active material may include both lithium nickel cobalt manganese oxide and lithium nickel cobalt aluminum oxide.

[0026] The embodiment of the present application also provides a secondary battery having an electrolyte matching the above-mentioned positive electrode material, comprising: a positive electrode plate, the positive electrode plate comprising the above-mentioned positive electrode material, wherein the positive electrode material comprises: a first active material of lithium manganese iron phosphate, and a second active material coated by the first active material, the chemical formula of the second active material is Li x Ni y Co z M k Me p O r A m , wherein 0.85≤x≤1.15, 0.81≤y≤0.91, 0<z<1, 0<k<1, 0≤p≤0.1, 1≤r≤2, 0≤m≤1, m+r≤2, y+z+k+p=1, M is selected from one or two of Mn and Al, Me is selected from one or more of Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, Nb, and A is selected from one or more of N, F, S, and Cl; and an electrolyte, wherein the percentage of vinylene carbonate (VC) in the electrolyte to the total mass of the electrolyte is greater than or equal to 1% and less than or equal to 4%. In some embodiments, the electrolyte does not contain dimethyl carbonate (DMC). For the secondary battery provided in the present application, by using the above-mentioned positive electrode material and making the percentage of vinylene carbonate (VC) in the electrolyte greater than or equal to 1% and less than or equal to 4% of the total mass of the electrolyte, the cycle performance of the secondary battery is significantly improved without the need to specially match different electrolyte designs.

[0027] Positive electrode

[0028] The positive electrode sheet in the secondary battery provided in the present application includes a positive electrode current collector and a positive electrode film layer arranged on the positive electrode current collector, the positive electrode film layer includes the positive electrode material described above, and the positive electrode current collector can be, for example, aluminum foil and nickel foil, however, other positive electrode current collectors commonly used in the art can be used. In some embodiments, the positive electrode film layer may also include a positive electrode conductor, a positive electrode binder, and a positive electrode dispersant. In some embodiments, the positive electrode conductor is one or more mixtures of conductive carbon black (SP), acetylene black, nano metal powder, carbon nanotubes, and graphene. In some embodiments, the positive electrode binder is one or more mixtures of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene, polytetrafluoroethylene, sodium carboxymethyl cellulose, and styrene-butadiene rubber. In some embodiments, the positive electrode dispersant includes one or more of polyvinyl pyrrolidone, polyethylene glycol, polyacrylic acid, and polyacrylate.

[0029] Electrolyte

[0030] The secondary battery also includes an electrolyte, which includes a lithium salt, a non-aqueous solvent and an additive, wherein the electrolyte does not contain dimethyl carbonate (DMC), and the percentage of vinylene carbonate (VC) in the electrolyte to the total mass of the electrolyte is greater than or equal to 1% and less than or equal to 4%.

[0031] The non-aqueous solvent may be a conventional non-aqueous solvent in the art, preferably an ester solvent, more preferably a carbonate solvent. The carbonate solvent is preferably one or more of ethylene carbonate, diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC) and butylene carbonate (BC).

[0032] The lithium salt may include at least one of LiPF6, LiBF4, LiN(SO2F)2 (abbreviated as LiFSI), LiClO4, LiAsF6, LiB(C2O4)2 (abbreviated as LiBOB), LiBF2(C2O4) (abbreviated as LiDFOB), LiN(SO2RF)2, LiN(SO2F)(SO2RF). Preferably, the content of the lithium salt in the electrolyte is 5% to 20%.

[0033] The additive includes at least vinylene carbonate (VC). In some embodiments, the additive also preferably includes one or more of fluoroethylene carbonate (FEC), vinyl ethylene carbonate (VEC), dithiothreitol (DTD), dithiothreitol, 1,3-propane sultone (PS), propene sultone and 1,4-butane sultone. The conventional amount of the additive in the electrolyte is 1% to 4% of the electrolyte, for example, 2%.

[0034] Negative electrode

[0035] In some embodiments, the secondary battery further comprises a negative electrode sheet, the negative electrode sheet comprising a negative electrode current collector and a negative electrode film layer disposed on the negative electrode current collector. In some embodiments, the negative electrode current collector may be copper foil. In some embodiments, the negative electrode film layer comprises a negative electrode active material, a negative electrode conductive agent, a negative electrode binder, and a negative electrode dispersant.

[0036] The negative electrode active material includes a negative electrode material capable of absorbing and releasing lithium (Li) (hereinafter, sometimes referred to as "a negative electrode material capable of absorbing / releasing lithium Li"). Examples of negative electrode materials capable of absorbing / releasing lithium (Li) may include carbon materials, metal compounds, oxides, sulfides, lithium nitrides such as LiN3, lithium metal, metals that form alloys with lithium, and polymer materials.

[0037] Carbon material can comprise low graphitized carbon, easy graphitized carbon, artificial graphite, natural graphite, mesophase carbon microsphere, soft carbon, hard carbon, pyrolytic carbon, coke, glassy carbon, organic polymer compound sintered body, carbon fiber and activated carbon. Wherein, coke can comprise pitch coke, needle coke and petroleum coke. Organic polymer compound sintered body refers to the material obtained by calcining polymer material such as phenol plastic or furan resin at appropriate temperature so that carbonization, some of these materials are divided into low graphitized carbon or easy graphitized carbon. The example of polymer material can comprise polyacetylene and polypyrrole.

[0038] Among these negative electrode materials capable of absorbing / releasing lithium (Li), further, materials with charge and discharge voltages close to those of lithium metal are selected. This is because the lower the charge and discharge voltage of the negative electrode material, the easier it is for an electrochemical device (such as a secondary battery) to have a higher energy density. Among them, carbon materials can be selected as negative electrode materials because their crystal structures have only small changes during charge and discharge, so good cycle characteristics and large charge and discharge capacity can be obtained. Graphite can be selected in particular because it can give a large electrochemical equivalent and a high energy density.

[0039] In addition, the negative electrode material capable of absorbing / releasing lithium (Li) may include single substance lithium metal, metal elements and semi-metal elements capable of forming alloys with lithium (Li), alloys and compounds of such elements, etc. In particular, they are used together with carbon materials, because in this case, good cycle characteristics and high energy density can be obtained. In addition to alloys including two or more metal elements, the alloys used here also include alloys containing one or more metal elements and one or more semi-metal elements. The alloy may be in the following states: solid solution, eutectic crystal (eutectic mixture), intermetallic compound and mixture thereof.

[0040] Examples of metal elements and semi-metal elements may include tin (Sn), lead (Pb), aluminum (Al), indium (In), silicon (Si), zinc (Zn), antimony (Sb), bismuth (Bi), cadmium (Cd), magnesium (Mg), boron (B), gallium (Ga), germanium (Ge), arsenic (As), silver (Ag), zirconium (Zr), yttrium (Y), and hafnium (Hf). Examples of the above alloys and compounds may include those having the chemical formula: Ma s Mb t Li u The material has the chemical formula: Ma p Mc q Md rIn these chemical formulas, Ma represents at least one of metal elements and semi-metal elements capable of forming an alloy with lithium; Mb represents at least one of metal elements and semi-metal elements other than lithium and Ma; Mc represents at least one of non-metal elements; Md represents at least one of metal elements and semi-metal elements other than Ma; and s, t, u, p, q and r satisfy s>0, t≥0, u≥0, p>0, q>0 and r≥0.

[0041] In addition, inorganic compounds that do not include lithium (Li), such as MnO2, V2O5, V6O 13 , NiS and MoS.

[0042] In some embodiments, the negative electrode conductive agent is one or a mixture of SP, acetylene black, nano silver powder, carbon nanotubes, and graphene. In some embodiments, the negative electrode binder is one or a mixture of vinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polytetrafluoroethylene, and styrene-butadiene rubber (SBR). In some embodiments, the negative electrode dispersant can be one or more of polyvinyl pyrrolidone (PVP), sodium carboxymethyl cellulose (CMC), and polyvinyl alcohol (PVA).

[0043] Isolation film

[0044] In some embodiments, the secondary battery further includes a separator, which is located between the positive electrode sheet and the negative electrode sheet. For example, the separator includes a separator of a substrate layer and a surface treatment layer; the substrate layer is a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate, and polyimide. Specifically, polypropylene porous film, polyethylene porous film, polypropylene non-woven fabric, polyethylene non-woven fabric, polypropylene-polyethylene-polypropylene porous composite film can be selected. A surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer can be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance.

[0045] Secondary battery

[0046] The positive electrode sheet, negative electrode sheet, electrolyte and separator described above can be assembled into a secondary battery by the commonly used method in the art, wherein the positive electrode sheet, separator, negative electrode sheet, etc. are wound or stacked in sequence into a bare battery cell, and then encapsulated in, for example, an aluminum-plastic film, and an electrolyte is injected. After formation, encapsulation and testing, the assembled secondary battery is subjected to electrochemical performance test and cycle performance test. The secondary batteries prepared in this application are all lithium-ion secondary batteries.

[0047] Those skilled in the art will understand that the above-described method for preparing a secondary battery is only an example, and other commonly used methods in the art may be used without departing from the contents disclosed in the present application.

[0048] The following describes a method for preparing a secondary battery.

[0049] (1) Preparation of positive electrode sheet

[0050] The positive electrode material, positive electrode conductor, positive electrode binder, positive electrode dispersant and N-methylpyrrolidone (NMP) are added to a stirring tank in a certain mass ratio and mixed evenly to obtain a positive electrode slurry, wherein the mass ratio of each component in the positive electrode slurry is: positive electrode material including the first active material and the second active material: 92%-96.5%, positive electrode conductor: 1%-3%, positive electrode binder: 1.5%-4%, positive electrode dispersant: 0.01-1%; and NMP is added according to the total mass of the positive electrode material, positive electrode conductor, positive electrode binder and positive electrode dispersant accounting for 45%-70% of the total mass of the positive electrode slurry; wherein the positive electrode material is lithium iron manganese phosphate (LiMn x Fe (1-x) PO4, wherein 0<x<1) and a ternary material, the ternary material comprising Li x Ni y Co z M k Me p O r A m , wherein 0.85≤x≤1.15, 0.81≤y≤0.91, 0<z<1, 0<k<1, 0≤p≤0.1, 1≤r≤2, 0≤m≤1, m+r≤2, y+z+k+p=1, M is selected from one or two of Mn and Al, Me is selected from one or more of Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, and Nb, A is selected from one or more of N, F, S, and Cl, such as but not limited to one or two mixtures of NCM ternary material nickel cobalt manganese oxide (wherein the nickel content is between 0.81≤y≤0.91) and NCA ternary material nickel cobalt aluminum oxide (wherein the nickel content is between 0.81≤y≤0.91), and the mass of lithium iron manganese phosphate in the positive electrode material accounts for greater than or equal to 70% and less than 100% of the total mass of the positive electrode material.

[0051] Then add the positive electrode slurry according to 0.3g-0.4g / 1540.25mm 2 The surface density is uniformly coated on the positive electrode current collector, and the positive electrode sheet is obtained after drying, rolling and slitting. Among them, after rolling and before slitting, the single-sided thickness of the positive electrode sheet is 79μm-124μm, and the compaction density is 2.1g / cm3 -2.45g / cm 3 between.

[0052] (2) Preparation of negative electrode sheet

[0053] The negative electrode material, negative electrode conductive agent, negative electrode binder, and negative electrode dispersant are fully stirred in a blender, and then NMP or deionized water is added and stirred to mix evenly to prepare the negative electrode slurry. The mass ratio of each component of the negative electrode slurry is: negative electrode material: 93%-98%, negative electrode conductive agent: 0.2%-1.5%, negative electrode binder: 1%-3%, and negative electrode dispersant: 0.01-1.5%; and NMP or deionized water is added according to the total mass of the negative electrode material, negative electrode conductive agent, negative electrode binder, and negative electrode dispersant accounting for 45%-70% of the total mass of the negative electrode slurry;

[0054] Then the negative electrode slurry is mixed according to 0.114-0.167g / 1540.25mm 2 The negative electrode sheet is uniformly coated on the negative electrode current collector, dried, rolled and cut to obtain the negative electrode sheet. After rolling and before cutting, the single-sided thickness of the negative electrode sheet is 52μm-75μm, and the density is 1.45g / cm 3 -1.8g / cm 3 between.

[0055] (3) Preparation of electrolyte

[0056] In an argon atmosphere glove box with a water content of <10ppm, fully dried lithium salt (LiPF6) is dissolved in an organic solvent and mixed evenly to obtain an electrolyte, wherein the concentration of LiPF6 is 1 mol / L, and vinylene carbonate (VC) and dimethyl carbonate (DMC) in the organic solvent are added as needed.

[0057] (4) Preparation of isolation membrane

[0058] It can be any of the above-mentioned isolation films, such as a 12 μm thick polypropylene isolation film.

[0059] (5) Preparation of batteries:

[0060] The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked or wound in sequence to obtain an electrode assembly, and the separator is placed between the positive and negative electrode sheets to play an isolating role. The electrode assembly is placed in a packaging shell, fully baked to make the water content below 450ppm, and then injected with electrolyte, sealed, inspected, and other processes to prepare a secondary battery.

[0061] The specific steps and conditions for formation are as follows: after the electrolyte is injected, maintain a hot pressing environment of 0.1MPa, charge at 0.02C for 17min at 45°C in a static state, stand for 5min and then charge to 0.3Ah at 0.02C, then cut off the air bag and vacuum seal, and stand at room temperature for 48h to complete the formation of the electrolyte.

[0062] Those skilled in the art will understand that the above-described method for preparing a secondary battery is only an example, and other commonly used methods in the art may be used without departing from the contents disclosed in the present application.

[0063] Some specific embodiments and comparative examples are listed below to better illustrate the present application.

[0064] Comparative Example 1

[0065] (1) Preparation of positive electrode sheet

[0066] The positive electrode material, the positive electrode conductor, the positive electrode binder, the positive electrode dispersant and N-methylpyrrolidone (NMP) are added to a stirring tank in a certain mass ratio and mixed evenly to obtain a positive electrode slurry, wherein the mass ratio of the positive electrode material, the positive electrode conductor acetylene black, the positive electrode binder PVDF, and the positive electrode dispersant (polyvinyl pyrrolidone) in the positive electrode slurry is 95:2:2:1, and NMP is added according to the total mass of the positive electrode material, the positive electrode conductor, the positive electrode binder and the positive electrode dispersant accounting for 50% of the total mass of the positive electrode slurry, wherein the positive electrode material is 70% lithium manganese iron phosphate (LiMn 0.6 Fe 0.4 PO4, the first active material and 30% NCM ternary material (Li 0.92 Ni 0.80 Co 0.08 M n0.11 Zn 0.01 O 1.21 Cl 0.72 , second active substance).

[0067] Then the positive electrode slurry is mixed according to 0.35g / 1540.25mm 2 (0.3g-0.4g / 1540.25mm 2 The positive electrode sheet is uniformly coated on the positive electrode current collector with a surface density of 79 μm (anywhere between 79 μm and 124 μm), and is dried, rolled, and cut to obtain a positive electrode sheet. After rolling and before cutting, the single-sided thickness of the positive electrode sheet is 79 μm (anywhere between 79 μm and 124 μm), and the compaction density is 1.1 g / cm 3 (at 1.1 g / cm 3 -1.45g / cm 3 Any between).

[0068] (2) Preparation of negative electrode sheet

[0069] The negative electrode material, the negative electrode conductive agent, the negative electrode binder, and the negative electrode dispersant are fully stirred in a mixer, and then NMP or deionized water is added and stirred to mix evenly to prepare the negative electrode slurry. Among them, in the negative electrode slurry, the mass ratio of the negative electrode material artificial graphite, the negative electrode conductive agent acetylene black, the negative electrode binder SBR, and the negative electrode dispersant PVP is 96:1:1.5:1.5, and NMP is added according to the total mass of the negative electrode material, the negative electrode conductive agent, the negative electrode binder and the negative electrode dispersant accounting for 50% of the total mass of the negative electrode slurry.

[0070] Then the negative electrode slurry is mixed according to 0.135g / 1540.25mm 2 (0.114-0.167g / 1540.25mm 2 The negative electrode sheet is uniformly coated on the negative electrode current collector with a surface density of 50 μm (anywhere between 52 μm and 75 μm), and is dried, rolled, and cut to obtain a negative electrode sheet. After rolling and before cutting, the single-sided thickness of the negative electrode sheet is 56 μm (anywhere between 52 μm and 75 μm), and the compaction is 1.6 g / cm 3 (at 1.45g / cm 3 -1.8g / cm 3 in between).

[0071] (3) Preparation of electrolyte

[0072] In an argon atmosphere glove box with a water content of <10ppm, a solution prepared in a mass ratio of 8:92 by mixing lithium salt LiPF6 with a non-aqueous organic solvent and additives (dimethyl carbonate (DMC), vinylene carbonate (VC)) and other additives (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP)) = 20:30:20:28, mass ratio) is used as an electrolyte for a secondary battery, wherein the concentration of LiPF6 is 1 mol / L, the DMC content in the electrolyte is 30%, and the VC content is 0.5%.

[0073] (4) Preparation of isolation membrane

[0074] A polyethylene (PE) porous polymer film is used as the isolation membrane.

[0075] (5) Preparation of secondary batteries

[0076] The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked or wound in sequence to obtain an electrode assembly, and the separator is placed between the positive and negative electrode sheets to play an isolating role. The electrode assembly is placed in a packaging shell, fully baked to make the water content below 450ppm, and then injected with electrolyte, sealed, inspected, and other processes to prepare a secondary battery.

[0077] Example 1

[0078] (1) Preparation of positive electrode sheet

[0079] The positive electrode material, the positive electrode conductor, the positive electrode binder, the positive electrode dispersant and N-methylpyrrolidone (NMP) are added to a stirring tank in a certain mass ratio and mixed evenly to obtain a positive electrode slurry, wherein the mass ratio of the positive electrode material (including the positive electrode active material), the positive electrode conductor acetylene black, the positive electrode binder PVDF, and the positive electrode dispersant (polyvinyl pyrrolidone) of the components of the positive electrode slurry is 95:2:2:1, and NMP is added according to the total mass of the positive electrode material, the positive electrode conductor, the positive electrode binder and the positive electrode dispersant accounting for 50% of the total mass of the positive electrode slurry, wherein the positive electrode material is 70% lithium manganese iron phosphate (LiMn 0.6 Fe 0.4 PO4, the first active material) and NCM ternary material (Li 0.92 Ni 0.86 Co 0.05 M n0.08 Zn 0.01 O 1.21 Cl 0.72 , the second active material), wherein the median particle size of the above-mentioned lithium iron manganese phosphate is 0.6-0.7μm, and the median particle size of the NCM ternary material (lithium nickel cobalt manganese oxide) is 6-7μm, and the lithium iron manganese phosphate is coated around the NCM ternary material (lithium nickel cobalt manganese oxide), and the cross-sectional perimeter of the coated NCM ternary material (lithium nickel cobalt manganese oxide) accounts for more than 90%. In addition, the median particle size of the primary particles of lithium iron manganese phosphate is 0.2-0.3μm.

[0080] Then the positive electrode slurry is mixed according to 0.35g / 1540.25mm 2 (0.3g-0.4g / 1540.25mm 2 The positive electrode sheet is uniformly coated on the positive electrode current collector with a surface density of 82 μm (between 79 μm and 124 μm), and is dried, rolled and cut to obtain a positive electrode sheet. After rolling and before cutting, the single-sided thickness of the positive electrode sheet is 82 μm (between 79 μm and 124 μm), and the compaction density is 2.3 g / cm 3 (at 2.1 g / cm 3 -2.45g / cm 3 in between).

[0081] (2) Preparation of negative electrode sheet

[0082] The negative electrode material, the negative electrode conductive agent, the negative electrode binder, and the negative electrode dispersant are fully stirred in a mixer, and then NMP or deionized water is added and stirred to mix evenly to prepare the negative electrode slurry. Among them, the mass ratio of the negative electrode material artificial graphite, the negative electrode conductive agent acetylene black, the negative electrode binder SBR, and the negative electrode dispersant PVP in the negative electrode slurry is 96:1:1.5:1.5, and NMP is added according to the total mass of the negative electrode material, the negative electrode conductive agent, the negative electrode binder and the negative electrode dispersant accounting for 50% of the total mass of the negative electrode slurry.

[0083] Then the negative electrode slurry is mixed according to 0.135g / 1540.25mm 2 (0.114-0.167g / 1540.25mm 2 The negative electrode sheet is uniformly coated on the negative electrode current collector with a surface density of 50 μm (anywhere between 52 μm and 75 μm), and is dried, rolled, and cut to obtain a negative electrode sheet. After rolling and before cutting, the single-sided thickness of the negative electrode sheet is 56 μm (anywhere between 52 μm and 75 μm), and the compaction is 1.6 g / cm 3 (at 1.45g / cm 3 -1.8g / cm 3 in between).

[0084] (3) Preparation of electrolyte

[0085] In an argon atmosphere glove box with a water content of <10ppm, a solution prepared in a mass ratio of 8:92 by mixing lithium salt LiPF6 with a non-aqueous organic solvent and additives (dimethyl carbonate (DMC), vinylene carbonate (VC)) and other additives (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP)) = 20:30:20:28, mass ratio) is used as an electrolyte for a secondary battery, wherein the concentration of LiPF6 is 1 mol / L, the DMC content in the electrolyte is 30%, and the VC content is 0.5%.

[0086] (4) Preparation of isolation membrane

[0087] A polyethylene (PE) porous polymer film is used as the isolation membrane.

[0088] (5) Preparation of secondary batteries

[0089] The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked or wound in sequence to obtain an electrode assembly, and the separator is placed between the positive and negative electrode sheets to play an isolating role. The electrode assembly is placed in a packaging shell, fully baked to make the water content below 450ppm, and then injected with electrolyte, sealed, inspected, and other processes to prepare a secondary battery.

[0090] Example 2

[0091] The preparation method is consistent with that of Example 1, except that the second active material of Example 2 uses NCM ternary material (lithium nickel cobalt manganese oxide, with a nickel content of 0.81).

[0092] Example 3

[0093] The preparation method is consistent with that of Example 1, except that the second active material of Example 3 uses NCM ternary material (lithium nickel cobalt manganese oxide, with a nickel content of 0.82).

[0094] Example 4

[0095] The preparation method is consistent with that of Example 1, except that the second active material of Example 4 uses NCM ternary material (lithium nickel cobalt manganese oxide, with a nickel content of 0.83).

[0096] Example 5

[0097] The preparation method is consistent with that of Example 1, except that the second active material of Example 5 uses NCM ternary material (lithium nickel cobalt manganese oxide, with a nickel content of 0.84).

[0098] Example 6

[0099] The preparation method is consistent with that of Example 1, except that the second active material of Example 6 uses NCM ternary material (lithium nickel cobalt manganese oxide, with a nickel content of 0.85).

[0100] Example 7

[0101] The preparation method is consistent with that of Example 1, except that the second active material of Example 7 uses NCM ternary material (lithium nickel cobalt manganese oxide, with a nickel content of 0.87).

[0102] Example 8

[0103] The preparation method is consistent with that of Example 1, except that the second active material of Example 8 uses NCM ternary material (lithium nickel cobalt manganese oxide, with a nickel content of 0.88).

[0104] Example 9

[0105] The preparation method is consistent with that of Example 1, except that the second active material of Example 9 uses NCM ternary material (lithium nickel cobalt manganese oxide, with a nickel content of 0.89).

[0106] Example 10

[0107] The preparation method is consistent with that of Example 1, except that the second active material of Example 10 uses NCM ternary material (lithium nickel cobalt manganese oxide, with a nickel content of 0.90).

[0108] Embodiment 11

[0109] The preparation method is consistent with that of Example 1, except that the second active material of Example 11 uses NCM ternary material (lithium nickel cobalt manganese oxide, with a nickel content of 0.91).

[0110] Example 12

[0111] The preparation method is consistent with that of Example 1, except that the DMC content in the electrolyte of Example 12 is 20%, and the VC content is 0.5%.

[0112] Example 13

[0113] The preparation method is consistent with that of Example 1, except that the DMC content in the electrolyte of Example 13 is 20%, and the VC content is 1%.

[0114] Embodiment 14

[0115] The preparation method is consistent with that of Example 1, except that the DMC content in the electrolyte of Example 14 is 10%, and the VC content is 2%.

[0116] Embodiment 15

[0117] The preparation method is consistent with that of Example 1, except that the electrolyte of Example 15 does not contain DMC and has a VC content of 1%.

[0118] Example 16

[0119] The preparation method is consistent with that of Example 1, except that the electrolyte of Example 16 does not contain DMC and has a VC content of 2%.

[0120] Embodiment 17

[0121] The preparation method is consistent with that of Example 1, except that the electrolyte of Example 17 does not contain DMC and has a VC content of 3%.

[0122] Embodiment 18

[0123] The preparation method is consistent with that of Example 1, except that the electrolyte of Example 18 does not contain DMC and has a VC content of 4%.

[0124] Embodiment 19

[0125] The preparation method is consistent with that of Example 1, except that the electrolyte of Example 19 does not contain DMC, and the VC content is 2%, and the median particle size of the first active material lithium manganese iron phosphate used in the positive electrode material is 0.5-0.6 μm.

[0126] Embodiment 20

[0127] The preparation method is consistent with that of Example 1, except that the electrolyte of Example 20 does not contain DMC, and the VC content is 2%, and the median particle size of the first active material lithium manganese iron phosphate used in the positive electrode material is 0.6-0.8 μm.

[0128] Embodiment 21

[0129] The preparation method is consistent with that of Example 1, except that the electrolyte of Example 21 does not contain DMC, and the VC content is 2%, and the median particle size of the first active material lithium manganese iron phosphate used in the positive electrode material is 0.8-0.9 μm.

[0130] Embodiment 22

[0131] The preparation method is consistent with that of Example 1, except that the electrolyte of Example 22 does not contain DMC, and the VC content is 2%, and the median particle size of the first active material lithium manganese iron phosphate used in the positive electrode material is 0.7-0.9 μm.

[0132] Embodiment 23

[0133] The preparation method is consistent with that of Example 1, except that the electrolyte of Example 23 does not contain DMC, and the VC content is 2%, and the median particle size of the second active substance NCM ternary material (lithium nickel cobalt manganese oxide) used in the positive electrode material is 5-6 μm.

[0134] Embodiment 24

[0135] The preparation method is consistent with that of Example 1, except that the electrolyte of Example 24 does not contain DMC, and the VC content is 2%. The median particle size of the second active substance NCM ternary material (lithium nickel cobalt manganese oxide) used in the positive electrode material is 7-8 μm.

[0136] Embodiment 25

[0137] The preparation method is consistent with that of Example 1, except that the electrolyte of Example 25 does not contain DMC, and the VC content is 2%. The median particle size of the second active substance NCM ternary material (lithium nickel cobalt manganese oxide) used in the positive electrode material is 6-8 μm.

[0138] Embodiment 26

[0139] The preparation method is consistent with that of Example 1, except that the electrolyte of Example 26 does not contain DMC, and the VC content is 2%, and the median particle size of the primary particles of the first active material lithium manganese iron phosphate used in the positive electrode material is 0.1-0.2 μm.

[0140] Embodiment 27

[0141] The preparation method is consistent with that of Example 1, except that the electrolyte of Example 27 does not contain DMC, and the VC content is 2%. The median particle size of the primary particles of the first active material lithium manganese iron phosphate used in the positive electrode material is 0.2-0.4 μm.

[0142] Embodiment 28

[0143] The preparation method is consistent with that of Example 1, except that the electrolyte of Example 28 does not contain DMC, and the VC content is 2%, and the median particle size of the primary particles of the first active material lithium manganese iron phosphate used in the positive electrode material is 0.3-0.4 μm.

[0144] Embodiment 29

[0145] The preparation method is consistent with that of Example 1, except that the electrolyte of Example 29 does not contain DMC and the VC content is 2%. The positive electrode material used is a mixture of 70% lithium manganese iron phosphate (the first active substance) and lithium nickel cobalt manganese oxide and lithium nickel cobalt aluminum oxide (the mass ratio of lithium nickel cobalt manganese oxide to lithium nickel cobalt aluminum oxide is 1:1) (the second active substance).

[0146] Embodiment 30

[0147] The preparation method is consistent with that of Example 1, except that the electrolyte of Example 30 does not contain DMC, and the VC content is 2%. The positive electrode material used is a mixture of 80% lithium manganese iron phosphate (first active substance) and lithium nickel cobalt aluminum oxide (second active substance).

[0148] Embodiment 31

[0149] The preparation method is consistent with that of Example 1, except that the electrolyte of Example 17 does not contain DMC, and the VC content is 2%, and the manganese (Mn) content of the first active material lithium manganese iron phosphate used in the positive electrode material is 0.7).

[0150] Embodiment 32

[0151] The preparation method is consistent with that of Example 1, except that the electrolyte of Example 18 does not contain DMC, and the VC content is 2%, and the manganese (Mn) content of the first active material lithium manganese iron phosphate used in the positive electrode material is 0.8).

[0152] Next, the testing process of the (lithium-ion) secondary battery is described.

[0153] (1) XRD test

[0154] The positive electrode sheets made in the comparative examples and embodiments were subjected to X-ray diffraction (XRD) test. X-ray diffraction (XRD) is mainly used to study the crystal structure inside the material, because X-rays have a wavelength close to the spacing between crystal planes and have a certain penetrating ability. A beam of X-rays passes through the crystal and diffracts, and then the diffraction pattern is analyzed to perform phase identification and structural analysis. Test working conditions: Cu Kα radiation, working current 250mA, continuous scanning, working voltage 40kV, scanning range 2θ 15-70°, step length 0.02, scanning speed 10°·min -1 .

[0155] (2) Gram capacity test

[0156] Take 5 secondary batteries in each of the comparative example and the example, charge them at room temperature at a constant current of 0.1C until the voltage reaches 4.3V, and then charge them at a constant voltage of 4.3V until the current is lower than 0.05C, so that they are in a fully charged state of 4.3V. Then discharge them at a constant current of 0.1C until the voltage reaches 3.0V.

[0157] (3) Secondary battery cycle performance test

[0158] Five secondary batteries prepared in the comparative example and the example were taken respectively, and the secondary batteries were repeatedly charged and discharged through the following steps, and the cycle capacity retention rate of the secondary batteries was calculated.

[0159] In an environment of 25°C, charge at a constant current of 0.5C (925mA) to 4.35V, then charge at a constant voltage of 4.35V to 0.05C (92.5mA), and then discharge at a constant current of 0.5C (925mA) to 3.0V, and record the discharge capacity of the first cycle; then perform 4000 charge and discharge cycles, and record the discharge capacity of the 4000th cycle.

[0160] Cycle capacity retention rate=(discharge capacity at the 4000th cycle / discharge capacity at the first cycle)×100%.

[0161] Table 1 shows the experimental results of Examples 1-11 and Comparative Example 1.

[0162] Table 1

[0163]

[0164]

[0165] By comparing Comparative Example 1 with Examples 1-11, it can be seen that the second active material (chemical formula is Li x Ni y Co z Mk Me p O r A m ) is between 0.81 and 0.91, the gram capacity of the corresponding secondary battery can be increased, and from Examples 1-11, it can be seen that when the second active material in the positive electrode material (chemical formula is Li x Ni y Co z M k Me p O r A m ) When the nickel content is between 0.82 and 0.86, the effect of improving the gram capacity is better.

[0166] In addition, in the present application, the second active material (chemical formula is Li x Ni y Co z M k Me p O r A m ) and the first active material (LiMn x Fe (1-x) The positive electrode material composed of PO4) can also improve the cycle performance of secondary batteries, but the improvement is limited and can only increase the cycle performance to about 80%.

[0167] Table 2 shows the experimental results of Examples 12-18 and Example 1.

[0168] Table 2

[0169]

[0170]

[0171] By comparing Example 1 and Examples 12-18, it can be seen that the smaller the DMC content in the electrolyte used in the secondary battery and the larger the VC content, the gram capacity and cycle performance of the secondary battery are further improved, and reach a maximum value when the electrolyte of the secondary battery does not contain DMC and the VC content is greater than or equal to 1% and less than or equal to 4%. Therefore, using an electrolyte matching the corresponding positive electrode material in the lithium-ion battery (does not contain DMC and the VC content is greater than or equal to 1% and less than or equal to 4%) can significantly improve the gram capacity and cycle performance of the secondary battery, and after 4000 cycles, the cycle capacity retention rate of the lithium-ion battery can still reach more than 85%.

[0172] Table 3 shows the experimental results of Examples 19-32 and Example 1.

[0173] Table 3

[0174]

[0175]

[0176] Note: Variables in Examples 26-28 are not shown in the table.

[0177] By comparing Example 1 and Examples 17-32, it can be seen that when the positive electrode material used in the secondary battery is matched with the electrolyte (does not contain DMC and has a VC content greater than or equal to 1% and less than or equal to 4% (such as 2%)), the median particle size of the first active substance (lithium iron manganese phosphate) is in the range of 0.5μm to 0.9μm, and the median particle size of the second active substance (lithium nickel cobalt manganese oxide and / or lithium nickel cobalt aluminum oxide) is in the range of 5μm to 8μm, and the median particle size of the primary particles of the first active substance is in the range of 0.1μm to 0.4μm, and the percentage of the first active substance in the total mass of the positive electrode material is greater than or equal to 70% and less than 100%, the gram capacity and cycle performance of the secondary battery can be significantly improved. After 4000 cycles, the cycle capacity retention rate can still reach more than 85%.

[0178] In addition, in the present application, by selecting a positive electrode material of a particle size range (the median particle size of the first active material (lithium manganese iron phosphate) is much smaller than the median particle size of the second active material (lithium nickel cobalt manganese oxide and / or lithium nickel cobalt aluminum oxide)) and making the cross-sectional perimeter of the coated second active material account for more than 90%, there are only small particles of the first active material around the second active material particles, and the large particles of the second active material play a similar role as a pillar in the first active material particles. Therefore, the positive electrode material of the present application reduces polarization by selecting large particles of the second active material and small particles of the first active material, and improves the compaction density by mixing large and small particles, and increases the compaction density to 2.1g / cm 3 -2.45g / cm 3 .

[0179] In summary, the secondary battery made of the positive electrode material provided in the present application has excellent gram capacity and cycle performance, and after 4000 charge and discharge cycles, it still has a capacity retention rate of more than 80%.

[0180] In addition, the present application further improves the cycle performance of the corresponding secondary battery by having a mutually matched positive electrode material and electrolyte, without the need to specially match different electrolyte designs. Specifically, after 4000 charge and discharge cycles, the capacity retention rate is still above 85%.

[0181] Those skilled in the art should understand that the above embodiments are merely exemplary embodiments and that various changes, substitutions and alterations may be made without departing from the spirit and scope of the present application.

Claims

1. A positive electrode material, characterized in that: include: A first active material, wherein the first active material is lithium manganese iron phosphate; as well as The second active material, the chemical formula of the second active material is Li x Ni y Co z M k Me p O r A m , wherein 0.85≤x≤1.15, 0.81≤y≤0.91, 0<z<1, 0<k<1, 0≤p≤0.1, 1≤r≤2, 0≤m≤1, m+r≤2, y+z+k+p=1, M is selected from one or two of Mn and Al, Me is selected from one or more of Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, and Nb, and A is selected from one or more of N, F, S, and Cl.

2. The positive electrode material according to claim 1, wherein 0.82≤y≤0.86。 3. The positive electrode material according to claim 1, wherein The median particle size of the first active material is smaller than the median particle size of the second active material.

4. The positive electrode material according to claim 1, wherein The median particle size of the first active material ranges from 0.5 μm to 0.9 μm, and the median particle size of the second active material ranges from 5 μm to 8 μm.

5. The positive electrode material according to claim 4, wherein The first active material is around the second active material, and the cross-sectional perimeter of the second active material covered by the first active material accounts for more than 90%.

6. The positive electrode material according to claim 1, wherein M is Mn or Al.

7. The positive electrode material according to claim 1, wherein The general formula of the lithium manganese iron phosphate is LiMn q Fe (1-q) PO4, where 0.6≤q≤0.

8.

8. The positive electrode material according to any one of claims 1, wherein The first active material accounts for a percentage of the total mass of the positive electrode material of greater than or equal to 70% and less than 100%.

9. The positive electrode material according to claim 3, wherein The median particle size of the primary particles of the first active material ranges from 0.1 μm to 0.4 μm.

10. A secondary battery, characterized in that: include: A positive electrode sheet, the positive electrode sheet comprising the positive electrode material according to any one of claims 1 to 9; Negative electrode; A separator, located between the positive electrode sheet and the negative electrode sheet; and An electrolyte, wherein the percentage of vinylene carbonate in the electrolyte to the total mass of the electrolyte is greater than or equal to 1% and less than or equal to 4%.

Citation Information

Patent Citations

  • Lithium-ion secondary battery anode and lithium-ion secondary battery

    CN101901892A

  • Blended cathode materials

    CN103828099A

  • Lithium manganese ferric phosphate doped ternary positive electrode active material, lithium ion battery and preparation method of lithium ion battery

    CN108321385A

  • Electrochemical devices and electronic devices containing them

    CN114938688A

  • Positive electrode active material, electrochemical device, and electronic apparatus

    CN115020696A